Utility-based non-cooperative power control game in wireless environment / Yousef Ali Mohammed Al-Gumaei - Yousef Ali, Mohammed Al-Gumaei (2017)
The spectrum resources, interference, and energy of battery-based devices are predominant problems and challenges in modern wireless networks. This thesis therefore addresses these issues by studying a theoretical framework for the design and analysis of distributed power control algorithms for modern cognitive radio and femtocell networks. It is shown that game theory tools are appropriate and efficient to develop scalable, balanced and energy-efficient, distributed power control schemes to be practically used in battery-based devices in wireless networks. Practically, the problem of power control is modelled as a non-cooperative game in which each user chooses its transmit power to maximize (or minimize) its own utility (or cost). The utility is defined as the ratio of throughput to transmit power, which is used to represent the energy efficiency scheme, whereas the cost is defined as the sum of the sigmoid weighting of transmit power and the square of the signal-to-interference ratio (SIR) error which is used to represent the SIR balancing scheme. Novel utility and cost functions proposed in this work are the method to derive efficient distributed power control algorithms. Also, the proposed pricing techniques in this thesis guide users to the efficient Nash equilibrium point by encouraging them to use network resources efficiently. These frameworks are more general and they are applied on cognitive and femtocell networks due to the critical and important issue of interference. Numerical simulations are used to prove the effectiveness of these algorithms compared with other existing power control algorithms. The simulated analytical and numerical results of this thesis indicate that the proposed algorithms can achieve a significant reduction of the user’s transmit power and thus a mitigation of the overall interference. Moreover, these algorithms have a relatively fast convergence rate and guarantee that all users can achieve their required QoS.